Exploring the Diverse Morphology of Porous Poly(Lactic Acid) Fibers for Developing Long-Term Controlled Antibiotic Delivery Systems - Kwon Ho Seo; Kyung Eun Lee; Meltem Yanilmaz; Juran Kim (MDPI AG, 2022)
In this study, we aimed to explore the morphologies of porous poly(lactic acid) (PLA) fibers through liquid-liquid phase separation, and investigate the relationship among pore formation, physical properties, and antibacterial activities of the fibers for identifying their potential as drug delivery carriers. Antibacterial activities of gentamicin-, kanamycin-, and amikacin-loaded PLA fibers against E. coli and S. epidermidis were evaluated. The antibacterial activity of drugs against E. coli showed the following profile: gentamicin > amikacin > kanamycin; however, S. epidermidis growth was almost completely inhibited immediately after the administration of all three drugs. The efficiency of gentamicin can be attributed to the electrostatic interactions between the positively and negatively charged antibiotic and bacterial cell membrane, respectively. Furthermore, gentamicin-loaded porous PLA fibers were evaluated as drug delivery systems. The cumulative amount of gentamicin in porous PLA nanofibers was considerably higher than that in other PLA fibers for 168 h, followed by 7:3 PLA > 6:4 PLA > 5:5 PLA > non-porous PLA. The 7:3 PLA fibers were projected to be ideal drug carrier candidates for controlled antibiotic release in delivery systems owing to their interconnected internal structure and the largest surface area (55.61 m2 g−1), pore size (42.19 nm), and pore volume (12.78 cm3 g−1).